2017
DOI: 10.1186/s12871-017-0436-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interscalene block on intraocular pressure and ocular perfusion pressure

Abstract: BackgroundInterscalene block (ISB) is commonly associated with Horner’s syndrome due to spread of local anesthetic to the cervical sympathetic chain. Postganglionic neurons that originate from superior cervical ganglia form the sympathetic innervation of eye. Decrease in sympathetic tone may change intraocular pressure (IOP) and ocular perfusion pressure (OPP). The aim of the study was to investigate whether ISB affects IOP and/or OPP.MethodsThirty patients scheduled for ambulatory shoulder surgery under regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Sensitivity analysis revealed that various anaesthetic agents significantly influenced fall in HRs. However, it made little difference to the overall results when study controls[ 29 30 33 34 35 37 39 40 41 42 43 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 ] and randomised trials[ 4 6 12 13 15 16 26 27 28 29 30 33 34 35 37 38 39 41 42 44 45 46 47 50 55 60 61 64 ] were analysed separately [ Table 2 ]. Meta-regression was performed since primary outcomes, characterised by significant heterogeneity, yielded statistically significant omnibus P values for statistical models considering different maintenance agents and opioids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity analysis revealed that various anaesthetic agents significantly influenced fall in HRs. However, it made little difference to the overall results when study controls[ 29 30 33 34 35 37 39 40 41 42 43 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 ] and randomised trials[ 4 6 12 13 15 16 26 27 28 29 30 33 34 35 37 38 39 41 42 44 45 46 47 50 55 60 61 64 ] were analysed separately [ Table 2 ]. Meta-regression was performed since primary outcomes, characterised by significant heterogeneity, yielded statistically significant omnibus P values for statistical models considering different maintenance agents and opioids.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to EHR,[ 6 15 16 29 33 34 35 37 38 39 40 42 43 44 45 46 47 49 51 52 54 55 56 57 58 65 ] MHR[ 16 29 33 34 35 36 38 41 43 46 48 49 50 51 53 54 55 56 57 58 59 60 61 62 63 64 66 ] and DHR[ 6 16 29 30 38 43 46 47 49 51 55 56 60 65 ] responses, meta-analysis showed a statistically significant fall in HR in subjects with GA (GA or GA + RA, P < 0.0001). Sensitivity analysis and meta-regressions confirmed that fentanyl significantly influenced the HR drop over time (meta-regression, estimates, 14.8, 9.8 and 16.9; standard error (SE) 5.3, 4.3 and 2.8; P = 0.007, 0.024 and <0.001; for early, mid and delayed periods, respectively) in GA subjects (Omnibus P < 0.001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISBPB-induced reduction in pupil size (miosis is one of the clinical signs of Horner's syndrome) is attributed to the blockade of the stellate ganglion, to which local anesthetic placed around the brachial plexus spreads from the interscalene groove along the prevertebral fascia [3].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical factors may also affect IOP readings, such as corneal thickness and stiffness 8 10 , mental stress 11 14 , circadian rhythm 15 , 16 , and the type of (e.g. general) anesthesia or sedation 17 – 21 . The use of sedatives is common practice in animal studies and clinical procedures 22 , but the effect of injectable sedatives on IOP has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%